Halal Tourism Development Strategy Using the Triple Helix Method (Case Study of Hubbul Wathan Mosque, Islamic Center of West Nusa Tenggara) - -, Ramadhi; Andi Amri; Iki Kurnia Illahi; Ferdino Wedi Sanjaya (Cattleya Darmaya Fortuna, 2025)
The development of halal tourism has recently gained significant attention among Indonesia's Muslim community. The potential to boost the local economy in halal tourism destinations is also highly promising. However, there is a lack of studies providing insights into effective strategies for developing halal tourism, making this research a novel contribution. The purpose of this study is to explore the development of the Hubbul Wathan Mosque at the Islamic Center of West Nusa Tenggara as a potential halal tourism destination using the Triple Helix method. The Triple Helix is a collaborative concept that supports the development of such sites through synergy among academia, government, and industry. This research employs a descriptive qualitative approach, involving respondents from mosque management, the local tourism office, and regional Islamic financial institutions. The findings indicate that the government plays a key role in formulating policies for the development and construction of the Hubbul Wathan Islamic Center, including legal frameworks that legitimize it as a halal tourism destination. These policies also enable Islamic financial institutions to act as sponsors and donors for various events held at the mosque. Meanwhile, the local community contributes to the maintenance of facilities and infrastructure, and is actively involved in religious services, education, economic activities, social programs, and Islamic outreach (dakwah). The implications of this study provide comprehensive information on collaborative strategies that can be applied in regions seeking to develop halal tourism